Use of fluorescent immunohistochemistry to investigate NF-κB involvement in brain pathologies - Padmanabhan, N. Rachel, author; Tjalkens, Ronald, advisor; Legare, Marie, committee member; Bouma, Gerrit, committee member (Colorado State University. Libraries, 2013)
Nuclear Factor Kappa Beta (NF-κB) is a transcription factor ubiquitously expressed in mammalian cells and involved in a broad spectrum of physiological responses. In the central nervous system (CNS), NF-κB is responsible for the regulation of several brain-specific processes, ranging from synaptic plasticity to neuroinflammation (Mattson and Camandola, 2001). The effects of NF-κB activation are highly variable and the transcription factor appears to play a dichotomous role in brain pathologies. Parkinson's Disease (PD) is the second most prevalent neurodegenerative disease in the world and is characterized by the progressive, irreversible loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc). Neuroinflammation, a CNS-specific immune response facilitated by glial cells, is now know to be an important contributing factor to PD pathology. Many neuroinflammatory responses have been linked to glial NF-κB activation, although the mechanisms have not yet been established. Drug-induced seizures are a serious adverse drug reaction (ADR) associated with both CNS- and non-CNS-targeting drugs. The current methods of drug safety evaluation rely solely on behavioral analysis and therefore often fail to identify potentially seizurogenic activity. Studies have suggested that neuronal NF-κB activation may be an early stress response and serve a neuroprotective function. The molecular mechanisms involved in seizurogenesis are also largely unknown. To study the role of NF-κB in these models of CNS injury, I employed fluorescent immunohistochemical (IHC) staining, a molecular technique that utilizes antibody-antigen binding to identify and visualize specific proteins in tissue. IHC has a wide range of applications and is often used for both laboratory research and clinical diagnostics. The following studies examined the role of NF-κB in CNS injury by using fluorescent IHC staining to characterize a transgenic mouse containing a NF-κB-driven enhanced green fluorescent protein (cis-NF-κBeGFP) construct in order to detect cell-specific changes in NF-κB activity. Using this method in the MPTP neurotoxin-induced model of Parkinson's Disease, I found that NF-κB-mediated glial activation accompanied loss of dopaminergic neurons and that treatment with novel pharmacological inhibitors of NF-κB attenuated this response. In the kainic acid (KA) model of drug-induced seizures, this method showed that neuronal activation of NF-κB occurs at sub-seizurogenic doses and may be an early, neuroprotective stress response. Fluorescent IHC staining in models of neuropathologies is useful for mechanistic research, but may also be an effective tool in drug-development. Use of fluorescent IHC with the NF-κB transgenic mouse allows for characterization of NF-κB signaling, as it relates to other proteins in vivo. Further optimization of this method could be extremely advantageous to NF-κB research.